Pancasila and Islamic Religious Education As Legal Culture Foundations: Building Legal Awareness and Compliance Through Islamic Sociological Jurisprudence Theory - Shafira Aulia Putri; Bintang Mufidia Rizqi; Naqiyyatul Aghni Nur Sya’ban; Ahmad Muhamad Mustain Nasoha (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to investigate the role of Pancasila and Islamic Religious Education (PAI) as a foundation for cultivating a legal culture within Indonesian society through the lens of Islamic Sociological Jurisprudence Theory. The motivation for this research arises from the low levels of legal awareness and compliance, which reveal a gap between existing legal norms and the social behaviors of the populace. The research employs a qualitative method with both conceptual and sociological approaches, which examines the fusion of Pancasila values and Islamic teachings in fostering internal and collective legal awareness. The findings indicate that Pancasila, as the foundational state philosophy, holds normative values that align with the principles of Islamic teachings in PAI, particularly in promoting social ethics and legal responsibility. Within the framework of Islamic Sociological Jurisprudence Theory, law is perceived not only as normative rules but also as a sociocultural phenomenon shaped by religious values and traditions. This integration can lead to a deeper legal consciousness, thereby encouraging compliance with the law that stems not from coercion but from the moral and religious awareness of the community. Hence, the collaboration between Pancasila, PAI, and the sociological approach of Islam proves to be an effective strategy for establishing a lasting legal culture in Indonesia.